A Comparison of Recovery Times Using Aldrete Score Between General Anesthesia Propofol and Ketamine - Putu Ayu Apriliani Trisna Dewi; R.Th Suprapromo; Ari Natalia Probandari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Intravenous anesthesia is an anesthetic agent that is administered intravenously, the advantages of using intravenous anesthetic agent is more convenient for patients and a short onset duration and recovery time. Propofol and ketamine are two intravenous anesthetic agent that is often used as an anesthetic induction or as the induction and maintenance of anesthesia in shor time surgical. After surgical procedure, patient must be kept under clinical observation at all times in a recovery facility until patient have reached normal level of consciousness. Level of consciousness after surgary can be measured by using Aldrete score that includes skin tone, respiration, circulation, level of consciousness and motor activity. The time required to recover fully normally ? 15 minutes. The objective of this study was to determine and to compare the recovery state between usage of general anesthesia propofol and ketamin. Methods: An analytical observational cross sectional study was conducted with both general anesthetics propofol and ketamin as independent variable and recovery state as dependent variable. Subjects recruited for this study were patients who underwent curatage surgery under intravenous anesthetics at Dr. Moewardi Regional General Hospital, Regional General Hospital of Ngipang, and Amanah Ibu Mother and Children Hospital. Subjects were selected using consecutive sampling technique. For the purpose of this study, recovery characteristics were measured using Aldrete score and were obtained after transported to a recovery room. Total subjects were 72, which were 36 subjects as propofol group and 36 subject as ketamin group. Statistical analyses were assessed by Chi square test using IBM SPSS 22.0. Results: This study found that 94,4% patients receiving propofol gained full recovery and 63,9% patients receiving ketamin gained full recovery as well. The statistical results stated that the p value is 0.001 (<0.05). Hence, statistically there was a significant difference between usage of general anesthesia propofol and ketamin. Conclusions: These findings statistically significant difference between usage of general anesthesia propofol and ketamin Keywords: aldrete score, recovery times, propofol, ketamin